Importance of haemonchosis in lamb rearing in a subhumid environment in Kenya: Preliminary results - Bullerdieck, P.; Peters, Kurt J.; Thorpe, W.R. (1990)
The study was carried out in three locations in the Mombasa region along the kenyan coast. A total of about 800 ewes (Dorper) were mated with Dorper and Red Maasai rams. Mating was restriced to a 6-week period and at night time only. Lambing seasons were targeted for March/April and November/December 1988. The ewes were divided into three antihelminthic treatment groups, the lambs being assigned to the treatment group of the dam, namely: animals treated intensively (Group A), animals treated individually when the PCV dropped below 29% (Group B) and animals treated when the PCV dropped to 20% or less (Group C). Within antihelminthic treatment groups, ewes and lambs were assigned to different types of supplementary feeding groups. Blood samples for PCV determination, faecal samples for helminth egg counts and the body weights were taken weekely from lambs upto the age of six months. While the sampling for adults were done monthly. The present analysis is limited to lambs of two locations:Diani and Nguni. The systematic effects of location and lambing season showed highly significant differences in weight gain of lambs. Genotype and sex affected weight gain significantly; only in some cases supplementary feeding of ewes had a positive effect on weight gain upto 30 days of age. Differences in weight gain due to supplementary feeding of lambs were not always significant between groups and were not persistent. Antilemintic treatment had a highly significant effect on weight gain. During the first days of life, only genotype shows a significant effect on PCV, the purebred lambs having a higher PCV than the crossbred lambs. At later ages, location, lambing season and antihelmentic treatment had highly significant influence on PCV. Supplementary feeding and sex had no significant effect on the PCV of lambs.